An Analytical Study of the Contemporary Applications of the Narrations of Ghazwah-e-Hind - Mr.Hafiz Muhammad Naveed Yousaf; Dr. Muhammad Imran (Journal of Religion and Society, 2025)
If the narrations regarding Ghazwah-e-Hind are examined carefully, it becomes evident that the Noble Prophet ﷺ not only encouraged the Companions (may Allah be pleased with them) to participate in Ghazwah-e-Hind, but also gave them glad tidings of victory in this expedition and promised Paradise to those who would take part in it. In the hadith of Abū Hurayrah, the Prophet ﷺ assured the Companions of this event, indicating his certainty that the people of Islam would indeed achieve victory in this battle.Moreover, in these narrations the term “ghazwah” has been used. Generally, the term ghazwah is applied to those battles in which the Prophet ﷺ personally participated. However, Ibn Ḥajar al-ʿAsqalānī writes that maghāzī is the plural of maghzā; its original form is ghazwah, and ghazā is an extended form of it. It is narrated from Thaʿlab that ghazwah represents the complete Sunnah of the Prophet ﷺ, and that the original meaning of ghazwah is intention and resolve. Here, by maghāzī is meant the Prophet’s ﷺ personal intention toward confronting the disbelievers, or his arranging and dispatching an army in his own name.According to Ibn Ḥajar al-ʿAsqalānī, a ghazwah is either a battle in which the Prophet ﷺ personally participated, or a campaign for which he himself organized and dispatched an army. When Ghazwah-e-Hind is examined in light of these definitions, it appears unlikely that this expedition took place during the apparent lifetime of the Prophet ﷺ. Since it is clear that this ghazwah did not occur during his lifetime, it is also established that the Prophet ﷺ did not personally participate in it.As for the second definition that a ghazwah is a battle for which the Prophet ﷺ personally organized and dispatched an army the pages of history are unable to provide evidence that the Prophet ﷺ sent any army for Ghazwah-e-Hind. However, it is certain that the Prophet ﷺ encouraged participation in this expedition and, along with that encouragement, also gave glad tidings regarding its eventual occurrence. Keywords: The Prophet's expeditions, the invasion of India, traditions, authentic status, contemporary applications, and effects